75 EVALUATING DEMENTIA PALLIATIVE CARE SERVICES ACROSS IRELAND AND THE UK USING THE RE-AIM FRAMEWORK. (25th October 2022) - Rukundo, A; Fox, S; Timmons, S; O'Connor, N; Guerin, S; Kernohan, G; Drennan, J; Murohy, A
Abstract: Background: Dementia is a life-limiting illness, requiring a Palliative Care (PC) approach from diagnosis. In Ireland, People with Dementia (PwD) and their families rarely receive PC in a timely manner. This study aimed to evaluate five exemplar community-based dementia PC services across Ireland and the UK (as identified by key stakeholders), to inform a new service delivery model. Methods: Data from semi-structured interviews and focus groups with 29 service providers, and service activity data (n=5), was evaluated using the RE-AIM framework. Results: 'Reach' - Caseloads varied significantly between 3-154 active cases. Most services accepted self-referrals; all wanted earlier referrals. Factors influencing reach included co-location, dyadic participation, service flexibility, and others' awareness of PC appropriateness and the service's existence. 'Effectiveness' - All service users received holistic assessments, person-centred care, advanced care planning, continuity of care, improved service access and 'care-for-the-carer'. Some services offered complimentary therapies, 24/7 phone support, and bereavement support; these were perceived to improve quality-of-life, comfort, and independence. 'Adoption' - Staff were highly invested; some provided their personal numbers to families. Outside staff were more willing to engage (refer/support) if shared governance, training was provided, or already familiar with dementia or the tools. Incentive programmes increased adoption rates. 'Implementation ' - All services evolved on an ad-hoc basis, with funding provided by local organisations, and a single 'driving force', typically a consultant/nurse. Services heavily relied on volunteers. Perceived "essential" elements included a dyadic approach, MDT involvement, open communication, forming relationships, reflective practices, dedicated staff with problem solving skills, and staff support/training. 'Maintenance' - All services continued after initial project funding; three increased their activities/reach over time. Conclusion: Important features and facilitators of community-based dementia palliative care services have been identified. These results are informing the development of the novel Dementia Palliative Care model for use in Ireland (https://pallcare4dementia.com/).